PENGARUH FAKTOR INTERNAL PELAKU USAHA TERHADAP KINERJA AGRIBISNIS HORTIKULTURA - Rasmikayati, Elly; Suminartika, Eti; Saefudin, Bobby Rachmat (Fakultas Pertanian Universitas Janabadra, 2026)
Horticultural agribusiness plays a strategic role in providing nutritious food and improving community income; however, small and medium-sized enterprises (SMEs) in this sector continue to face various constraints that affect business performance. This study aims to analyze the effects of internal factors, namely entrepreneurs’ personal characteristics, entrepreneurial motivation, social support, opportunity recognition and exploitation, and entrepreneurial competence on the performance of horticultural agribusinesses. A quantitative approach with a descriptive–correlational design was employed through a survey of 109 horticultural business actors in West Java, DKI Jakarta, Banten, and Central Java. Data were collected using a 1–5 Likert-scale questionnaire and analyzed using descriptive statistics, index-score analysis, and multiple linear regression. The descriptive results indicate that the highest average index score was found for entrepreneurs’ personal characteristics (4.121), while overall agribusiness performance was moderate (3.084), with the lowest scores observed in business volume growth and market share growth. The regression model show that entrepreneurial competence had a positive and significant effect on business performance, whereas the other internal variables were not significant. Practically, the study suggests strengthening technical and managerial competencies, implementing more applied institutional mentoring, and adopting market expansion strategies to enhance business volume and market share.